Marine Genetic Resources in Areas Beyond National Jurisdiction: Access and Benefit-Sharing - Kexin Zhu (Studies in Law and Justice, 2023)
At present, the international community has held many discussions on the exploitation and utilization of marine genetic resources in area beyond national jurisdiction, and this issue has gradually become a hot topic in the field of international law of the sea. The first part of the main text introduces the negotiation dilemma of benefit-sharing of marine genetic resources with respect to the basic concept and legal status of MGRs in the ABNJ, and the second part summarizes the dilemma of negotiation on benefit-sharing of MGRs in the context of BBNJ, and focuses on the reasons for such dilemma. The third part discusses breakthroughs of the legal dilemma of MGRs in the ABNJ from a practical point of view and concludes with an assessment of the options within existing legal frameworks for accommodating an access and benefit-sharing system for marine genetic resources originating from ABNJ.